The Gambia : Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2006)
This paper focuses on the Staff-Monitored Program (SMP) for The Gambia. Understandings have been reached with the authorities on the SMP covering the period October 1, 2005 to March 31, 2006. Key objectives of the program include making progress toward fiscal sustainability, strengthening internal controls and the operational independence of the Central Bank of The Gambia, and enhancing public financial management and accountability. Successful implementation of the SMP should pave the way for reaching understandings on a possible new arrangement under the Poverty Reduction and Growth Facility (PRGF).